The Effects of Transcranial Direct Current Stimulation (tDCS) on Working Memory Training in Healthy Young Adults - Ke, Yufeng; Wang, Ningci; Du, Jiale; Kong, Linghan; Liu, Shuang; Xu, Minpeng; An, Xingwei; Ming, Dong (Frontiers in Human Neuroscience, 2019)
Working memory (WM) is a fundamental cognitive ability to support complex thought, but it is limited in capacity. WM training has shown the potential to make benefit for those in need. Many studies have shown the potential of transcranial direct current stimulation (tDCS) to transiently enhance WM performance by delivering low current to the brain cortex of interest via electrodes on the scalp. TDCS has also been revealed as a promising intervention to augment WM training in a few studies. However, those few tDCS-paired WM training studies focused more on the effect of tDCS on WM enhancement and its transferability after training but paid less attention to the variation of cognitive performance during the training procedure. The current study attempted to explore the effect of tDCS on the variation of performance during WM training in healthy young adults. All the participant received WM training with the load-adaptive verbal N-back task for five days. During the training procedure, active/sham anodal high-definition tDCS (HD-tDCS) was used to stimulate the left dorsolateral prefrontal cortex (DLPFC). To examine the training effect, pre- and post-test were performed respectively one-day before and after the training sessions respectively. At the beginning of each training session, stable-load WM tasks were performed to examine the performance variation during training. Compared to the sham stimulation, higher learning rates of performance metrics during the training procedure were found when WM training was combined with active anodal HD-tDCS. The performance improvements (post-pre) of the active group were also found to be higher than those of sham group and were transferred to a similar untrained WM task. Further analysis revealed that the negative relation between the training improvements and baseline performance. These findings show the potential that tDCS may be leveraged as an intervention to facilitate WM training for those in need of higher WM ability.